以点\( (2, - 1,2) \) 为球心,3为半径的球面方程为( )
A: \( {\left( {x + 2} \right)^2} + {(y - 1)^2} + {(z + 2)^2} = 9 \)
B: \( {\left( {x + 2} \right)^2} + {(y - 1)^2} + {(z + 2)^2} = 3 \)
C: \( {\left( {x - 2} \right)^2} + {(y + 1)^2} + {(z - 2)^2} = 9 \)
D: \( {\left( {x - 2} \right)^2} + {(y + 1)^2} + {(z - 2)^2} = 3 \)
A: \( {\left( {x + 2} \right)^2} + {(y - 1)^2} + {(z + 2)^2} = 9 \)
B: \( {\left( {x + 2} \right)^2} + {(y - 1)^2} + {(z + 2)^2} = 3 \)
C: \( {\left( {x - 2} \right)^2} + {(y + 1)^2} + {(z - 2)^2} = 9 \)
D: \( {\left( {x - 2} \right)^2} + {(y + 1)^2} + {(z - 2)^2} = 3 \)
举一反三
- 以点\( (2, - 1,2) \)求球心,3为半径的球面方程为( ) A: \( {(x + 2)^2} + {(y - 1)^2} + {(z + 2)^2} = 9 \) B: \( {(x + 2)^2} + {(y - 1)^2} + {(z + 2)^2} = 3 \) C: \( {(x - 2)^2} + {(y + 1)^2} + {(z - 2)^2} = 9 \) D: \( {(x - 2)^2} + {(y + 1)^2} + {(z - 2)^2} = 3 \)
- 设\(f\left( {x,y,z} \right) = x{y^2} + y{z^2} + z{x^2}\),则\({f_{yz}}\left( {0,-1,0} \right) = \)( ) A: 1 B: 0 C: -1 D: 2
- 设\(z = \int_ { { x^2}}^y { { e^t}\sin t} dt\),则\({z_{xx}=}\) A: \(2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\sin {x^2} + 2{x^2}\cos {x^2}} \right]\) B: \( - 2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\sin {x^2} - 2{x^2}\cos {x^2}} \right]\) C: \( - 2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\sin {x^2} + 2{x^2}\cos {x^2}} \right]\) D: \( - 2{e^ { { x^2}}}\left[ {\left( {1 + 2{x^2}} \right)\cos {x^2} + 2{x^2}\sin {x^2}} \right]\)
- 曲线\( \left\{ {\matrix{ { { x^2} + {y^2} = {z^2}} \cr { { z^2} = y} \cr } } \right. \)在坐标面\( yoz \) 上的投影曲线方程为( ) A: \( \left\{ {\matrix{ { { x^2} + { { \left( {y - {1 \over 2}} \right)}^2} = {1 \over 4}} \cr {z = 0} \cr } } \right. \) B: \( \left\{ {\matrix{ { { z^2} = y} \cr {x = 0} \cr } } \right. \) C: \( \left\{ {\matrix{ {z = {y^2}} \cr {x = 0} \cr } } \right. \) D: \( \left\{ {\matrix{ { { y^2} + { { \left( {x - {1 \over 2}} \right)}^2} = {1 \over 4}} \cr {z = 0} \cr } } \right. \)
- 设\(z = z\left( {x,y} \right)\)是由方程\({z^3}{\rm{ + }}3xyz - 3\sin xy = 1\)确定的隐函数,则\( { { \partial z} \over {\partial y}}=\)( ) A: \( { { y\left( {\cos xy - z} \right)} \over { { z^2} + xy}}\) B: \( { { y\left( {z - \cos xy} \right)} \over { { z^2} + xy}}\) C: \( { { x\left( {\cos xy - z} \right)} \over { { z^2} + xy}}\) D: \( { { x\left( {z - \cos xy} \right)} \over { { z^2} + xy}}\)